MEMEGWAANH, Indigenous Co-Curricular Honour Program - Di Lulio, Camille (Scholarship@Western, 2021)
One response to the Truth and Reconciliation Commissions’ 94 Calls to Action report (2015) are co-curricular initiatives that aim to Indigenize the student experience. Previous research has shown that cocurricular achievements increase students’ self-awareness of their skill set, which helps them to better articulate skills to future employers. Western University’s Office of Indigenous Initiatives proposes Memegwaanh (Meh-meh-gwah, translated to “butterfly” in Anishinaabemowin), the Indigenous Co-Curricular Honour Program, offered to all undergraduate students at main campus and the affiliates. The co-curricular program aims to develop students’ awareness and knowledge of Indigenous identity and gain a comprehensive understanding of the relational history between Indigenous Peoples and the nation of Canada. Students are rewarded with recognition on their formal academic transcript, following completion of activities across four categories: a) academic coursework, b) community-engaged experiential learning, c) the completion of NVision’s “The Path”, and d) participating in workshops through the Office of Indigenous Initiatives. Framed in a decolonizing theoretical lens, the curriculum planning process is led by and collaborated with Indigenous Peoples, with expressed intent to privilege the Indigenous perspective. This approach aims to support Indigenous Peoples’ right to self-determination, to protect the integrity and authenticity of cultural content, and to honour the lived PAGE 19 experiences of Indigenous Peoples. Students completing the program are better equipped to identify ways to engage in cross-cultural relationships and support reconciliation in alignment with the Truth and Reconciliation Commission’s Calls to Action. https://ir.lib.uwo.ca/headandheartprogram_2021/1002/thumbnail.jpg